Presentation and treatment of Vitamin D deficiency. (24th May 2012) - Subbaraya, N; Lygo, N; Forster, J; Shenoy, S
Abstract : Aim: To evaluate the adequacy and safety of current recommended dosage of Vitamin D (VitD) treatment in children diagnosed with vitamin D deficiency (vitDD) and role for routine follow-up VitD levels following treatment. Method: Retrospective audit of all children (0-16 years) diagnosed to have VitDD and received treatment, according to local guidelines, during 18 month period (Jan 2010-June 2011). Data on demographics, investigation, treatment and follow-up VitD levels were analysed. Dose of Cholecalciferol was that recommended in children's British National Formulary (cBNF). Results: 137 children fulfilled the criteria. 28% < 6 months age at diagnosis, 22% over 12 years and 50% within 6 m – 12 years age group. 80% (N=117) were South Asian (SA) ethnicity. There was equal distribution of cases throughout the year. 47% had no other underlying medical issues. 44% (N=60) were asymptomatic. 34 infants <6 months age were asymptomatic and diagnosed to have VitDD during prolonged jaundice screening. Bone pain was the most frequent presenting symptom amongst those symptomatic. 53% were severe deficient (VitD < 15 nmol/l), 32% deficient (15-30 nmol/l) and 15% insufficient (30-50 nmol/l). There was no significant difference in the severity of deficiency between asymptomatic and symptomatic groups. All received treatment for 8 weeks duration except 9% for 6 weeks (all had insufficiency rather than deficiency). 83% (N = 84) had followup VitD levels after treatment. 93% achieved levels within 'ideal' range (50-150 nmol/l) whilst 7% failed to achieve (compliance issue identified in all). 6 of the 20 children under 6 months age had followup level above the ideal range up to 200 nmol/l but not toxic level (> 500 nmol/l). Conclusions: VitDD is very common in children of SA ethnicity. Children with severe VitDD can be asymptomatic. Dose of Cholecalciferol recommended in cBNF for a period of 8 weeks to correct VitDD is safe to use except those under 6 months where a 6 week course is adequate. Routine followup VitD levels after treatment is not necessary unless compliance with treatment is considered and in those children <6 months age until further evidence of safety in this age group.